Developing Natural and Social Science Books Integrating Science Process Skills to Enhance Student Learning Outcomes in Fifth Grade Elementary School - Daulai, Nurmayani; Sari, Siti Mayang; Akmaluddin (Jurnal Komunikasi Pendidikan, 2024)
Existing textbooks in elementary education often fail to engage students fully and do not effectively enhance their science process skills. This research aims to develop science and social studies books based on science process skills to improve the learning outcomes of fifth-grade elementary school students. Observations reveal that current textbooks are not sufficiently engaging and fail to enhance students' science process skills. Using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) method, this research and development study produced a Science Process Skills Based Science book. The results show that this book significantly improves student learning outcomes, with students achieving an average score of 88, exceeding the minimum completeness criteria of 75. The book's validity is rated as very feasible, and 88% of students met the very good criteria, with 29 students completing the standard. The study concludes that quality teaching incorporating science process skills greatly enhances student learning outcomes, making learning activities more meaningful and effective. This research contributes to education by providing a validated resource that fosters essential science skills development in elementary students.